Literary Education: a Reading Proposal - Cousillas Pena, Paula (Madrygal. Revista de Estudios Gallegos, 2019)
Literary education is one of the blocks that structure the education curriculum of the subject Galician Language and Literature, in which a double objective is contemplated: on the one hand, the approach to history, works and the most salient literary figures; and, on the other hand, the purpose of reaching competent readers who will continue their reading training. However, the observation of different educational programs, in which each teacher indicates the treatment of reading in classrooms, states that in most cases only the historicist approach is perpetuated, and does not encourage a taste for reading and student-reader training. Thus, the objective of this work is to offer a methodological alternative that allows to incorporate reading in the classroom in a different way to how it has been done frequently in educational centers. In this sense, through the methodology of the literary constellation, an annual reading proposal has been prepared for students of 2nd ESO in the subject of Lingua Galician Literature, with the purpose of responding to the needs of a proper training literary, in which the students develop not only the contents and the competences indicated in the curriculum, but also enhance the reading habit and an adequate literary-literary competence.